1985
DOI: 10.1007/bf02370167
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic RNA transport

Abstract: A number of closely related post-transcriptional facets of RNA metabolism show nuclear compartmentation, including capping, methylation, splicing reactions, and packaging in ribonucleoprotein particles (RNP). These nuclear 'processing' events are followed by the translocation of the finished product across the nuclear envelope. Due to the inherent complexity of these interrelated events, in vitro systems have been designed to examine the processes separately, particularly so with regard to translocation. A few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 185 publications
(134 reference statements)
0
18
0
Order By: Relevance
“…By using isolated nuclei many groups have shown that release of endogenous RNP complexes is temperature and energy dependent, suggesting active transport (2,15). The in vitro rate of RNP efflux has been correlated with the level of activity of a particular nuclear envelope NTPase; the NTPase is stimulated by exogenous RNA but its exact function is unknown (2,7,15).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By using isolated nuclei many groups have shown that release of endogenous RNP complexes is temperature and energy dependent, suggesting active transport (2,15). The in vitro rate of RNP efflux has been correlated with the level of activity of a particular nuclear envelope NTPase; the NTPase is stimulated by exogenous RNA but its exact function is unknown (2,7,15).…”
mentioning
confidence: 99%
“…The in vitro rate of RNP efflux has been correlated with the level of activity of a particular nuclear envelope NTPase; the NTPase is stimulated by exogenous RNA but its exact function is unknown (2,7,15). Further evidence for a facilitated transport mechanism was obtained by Zasloff who showed by microinjection of tRNAs into Xenopus oocyte nuclei that the export rate was saturable and sensitive to temperature (60).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus important to consider tant splicing must occur within highly organized ribonucleoprotein multicomponents, somewhat analogous to ribosomes (Brody and Abelson, 1985 ;Grabowski et al, 1985 ;Frendewey and Keller, 1985 (Nevins, 1983) and poly(A) addition (Huez et al, 1981) have been suggested as protecting RNA against nucleolytic degradation. Mature RNA is then transported into cytoplasm through the nuclear pore complex (for a recent review see Clawson et al, 1985). The precise mechanism of transport remains unknown, but it does exhibit selectivity towards correctly processed mRNA (Webb et al, 1981) or rRNA (Wunderlich, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate splicing of pre-RNA to mature RNA is apparently a prerequisite for nucleocytoplasmic transport. RNA transport is also an energy-dependent process and involves a nucleoside triphosphatase associated with nuclear envelope and matrix (Clawson et al, 1985).…”
Section: Introductionmentioning
confidence: 99%